Gambaran Ketepatan Enam Benar Pemberian Obat Berbasis Electronical Medical Record Di Ruang Rawat Inap Anak - Gesti Rukmini; Tuti Asrianti Utami; Rosa Nora Lina (Akademi Farmasi Yarsi Pontianak, 2022)
The accuracy of drug administration is the most important thing for patient safety, especially in children. Accuracy of six correct in the administration of drugs based on Electronic Medical Record (EMR) is one form of performance from a nurse. Errors in drug administration will have a fatal impact on patient safety in the hospital. The purpose of this study was to describe the accuracy of the six correct EMR-based drug administrations in the children's inpatient ward of Hospital X Tangerang. This study uses a descriptive correlation method with a cross-sectional approach. The research sample with a total sampling of 30 nurses. The results of this study explain that most of the nurses aged 25-35 years as much as 60%, 60% D3 nursing education and work period >10 years as much as 40%. The distribution of the frequency of the application of the six correct drug administration by nurses based on the principle of the correct drug has been applied as much as 93.3%. The application of accuracy in drug administration is for the right dose as much as 86.7%, on-time 83.3%, the right patient 83.3%, the right way/route as much as 86.7% and the right documentation as much as 93.3%. It is important for nursing services in the administration of electronic medical record (EMR)-based drugs to be carried out properly, especially in the pediatric inpatient room. Increased EMR supervision is required by implementing internal and external training so that errors in drug administration do not occur.